2022
DOI: 10.1177/18632521221117445
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcomes of proximal humerus fractures in children and adolescents: A systematic review

Abstract: Purpose: Minimally displaced pediatric proximal humerus fractures can be reliably managed non-operatively; however, there is considerable debate regarding the appropriate management of severely displaced proximal humerus fractures, particularly in older children and adolescents with limited remodeling potential. The purpose of this study was to perform a systematic review to answer the questions: “What are the functional and quality-of-life outcomes of pediatric proximal humerus fractures?” and “What factors h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…It is well known that proximal humeral fractures heal well in young children; however, less is known in adolescents. A recent systematic review found that, since the 1946 inception date in the National Library of Medicine’s computer-based retrospective search service, there have only been 4 prospective cohort studies and 8 retrospective cohort studies examining proximal humeral fractures in children 1 . None has explicitly focused on fractures occurring during adolescence.…”
Section: Commentarymentioning
confidence: 99%
“…It is well known that proximal humeral fractures heal well in young children; however, less is known in adolescents. A recent systematic review found that, since the 1946 inception date in the National Library of Medicine’s computer-based retrospective search service, there have only been 4 prospective cohort studies and 8 retrospective cohort studies examining proximal humeral fractures in children 1 . None has explicitly focused on fractures occurring during adolescence.…”
Section: Commentarymentioning
confidence: 99%
“… 7 , 8 Nevertheless, the treatment of NH grade 3 and 4 in adolescents approaching skeletal maturity is debatable in current literature. 9 , 10 Several treatment guidelines have been formulated from expert groups for the treatment of PHF based on the patients’ age, the extent of fracture displacement, and comorbidities. 10 14 Neurovascular injury and open fractures are the only absolute reasons for surgical treatment in skeletally immature patients with PHFs.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Currently, no consensus and no evidence-based guideline have been published concerning treatment options in dependence of patient age, fracture severity, and grade of displacement. 9 , 15 , 16 In recent years, many authors have expanded the relative indications for surgical treatment especially in adolescents approaching skeletal maturity with highly displaced PHF. 9 , 10 , 14 , 16 In our opinion, this broadening of the indications of surgical treatment is possibly related to observed poor clinical outcomes in older children with highly displaced fractures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations